Metabolic syndrome in Italy: a pilot study - Cornelli, U.; Belcaro, G.; Cesarone, M. R.; Di Rienzo, A.; Cornelli, M.; Bamonti, F.; Ledda, A. (Progress in Nutrition, 2007)
Objective: The Metabolic Syndrome (MS) in relation to the Mediterranean Diet in a sample of the Italian population. Method: A pilot study was carried out in 10 different towns in Italy on 307 subjects of both sexes (age between 20 and 85 years) using a Mobile Unit (MU) for the collection of history, anthropometric data, vital indexes, echocardiography and the laboratory surveys of the subjects. The prevalence of MS was determined according to ATPIII. The diet was monitored by a questionnaire based on the analysis of 9 categories of food (9TF); anthropometric and vital indexes, echocardiography and lab assessment were carried out by the same team using the instruments of the MU. Results: The prevalence of MS was 18.5% (with no relevant gender differences. In subjects with MS the age was 9 years higher in males (65 vs 56 years) and 14 years in females (64 vs 50 years); the height was lower of 3 cm; school attendance was significantly reduced; sedentariness seems not to be discriminant since it is present in most of the cases with or without MS; cereal consumption was significantly higher for both genders; alcool consumption was higher in males and lower in females (as a trend); energy intake was significantly higher in males only; carotid wall thickening was significantly more severe with no gender differences. Age correction is flattening some of the differences but did not substantially affect the alimentary parameters. Conclusions: The MS is present in subjects who follow the Mediterranean Diet, particularly when energy intake is rich in carbohydrates. The use of fruits and vegetables does not decrease its prevalence. Other elements such as age, genetics, and school attendance are important for its expression.